2022
DOI: 10.2147/jir.s378309
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Status of SII and SIRI Alters the Risk of Cardiovascular Diseases: Evidence from Kailuan Cohort Study

Abstract: Background: Two novel systemic inflammation indices, SII and SIRI, are associated with increased risk of cardiovascular diseases (CVD). However, SII and SIRI are prone to change over time and the association between changeable status and long-term outcome risk remains to be uncovered. This study aims to examine the association between the dynamic status of SII and SIRI and risk of CVD. Methods: This prospective study included a total of 45,809 subjects without MI, stroke and cancer prior to or in 2010 (baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Karadeniz et al also found that a higher TyG index was strongly associated with major cardiovascular adverse events [ 43 ]. Another large prospective study found a significant association between a large increase in the SII index and the risk of CVDs [ 44 ]. Our study also showed that the combination of the above markers still had good efficacy in predicting CVDs, and reference to these markers can better assess the risk of CVDs in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Karadeniz et al also found that a higher TyG index was strongly associated with major cardiovascular adverse events [ 43 ]. Another large prospective study found a significant association between a large increase in the SII index and the risk of CVDs [ 44 ]. Our study also showed that the combination of the above markers still had good efficacy in predicting CVDs, and reference to these markers can better assess the risk of CVDs in patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may limit generalization of these results. Third, the SII value is dynamic, and its dynamic status has been found to be associated with risk of cardiovascular diseases (40). In this study, we only used the SII data on admission, which may lead to underestimate this association (35).…”
Section: Discussionmentioning
confidence: 99%
“…As a combination of NLR and MLR, SIRI is a newly discovered inflammatory biomarker, which plays an independent predictive role in the diagnosis and prognosis assessment of cancer, rheumatoid arthritis and stroke [ 21–23 ]. Previous studies have demonstrated that SIRI levels were closely associated with increased cardiovascular disease risk [ 10 , 11 ]. Han et al.…”
Section: Discussionmentioning
confidence: 99%